Luminol-based electrochemiluminescent biosensors for highly sensitive medical diagnosis and rapid antioxidant detection. (16th February 2018) - Tamiya, Eiichi; Inoue, Yuki; Saito, Masato
Abstract: We present a review of luminol-based electrochemiluminescence (ECL) biosensors that perform enzymatic reactions and bioanalysis using antioxidant molecules by controlling the spatiotemporal production of a luminescent substrate, catalase activity, and glycated albumin (GA). The ECL intensity depends on the antioxidant capacity because radicals are neutralized by the antioxidants, which suppresses the luminescence. The antioxidant capacities of 22 types beverages were evaluated by comparison with a standard curve of Trolox. The time necessary for the ECL measurement of the antioxidant capacity is only 2 min with screen-printed electrodes and a portable ECL measurement system. Our system was also used to monitor reactive oxygen species released from neutrophils, which play an important role in the immune system, defending against viral and bacterial infections. The quenching of ECL imaging by catalase reaction localized in the multichamber electrode using the electrogenerated substrate was examined as a potential candidate for a sensitive reporting system. The substrate was successfully generated at applied potentials between −1 and −0.4 V in multichamber electrodes and the substrate confinement within the chamber was observed within 60 s of generation. The microchamber electrode system demonstrated a detection limit of 90 fM catalase. We also demonstrated a detection limit of 0.1 µM GA in human serum albumin, which is an improvement of about 70 times over colorimetric methods.